Combination of microwave-assisted extraction and ultrasonic-assisted dispersive liquid-liquid microextraction for separation and enrichment of pyrethroids residues in Litchi fruit prior to HPLC determination. (1st February 2018) - Wang, Ke; Xie, Xiujuan; Zhang, Yi; Huang, Yuanxiang; Zhou, Shiyu; Zhang, Wei; Lin, Yuyang; Fan, Huajun
Highlights: Combining MAE with UADLLME and HPLC for simultaneous determination of pyrethroids residues in Litchi fruit. Extraction conditions of MAE and UADLLME were optimized by single-factor experiments and RSM. Extraction yields and enrichment factors of pyrethroids were improved by MAE-UADLLME. The distribution of pyrethroids residues in the pericarp and the pulp was investigated. Abstract: A novel method for simultaneous determination of pyrethroids residues in Litchi fruit has been developed by HPLC-UV detection using microwave-assisted extraction (MAE) coupled with ultrasonic-assisted dispersive liquid-liquid microextraction (UADLLME). Extraction conditions of MAE and UADLLME were respectively investigated by single-factor experiments and response surface methodology. Optimized experimental conditions included 310 μL of chlorobenzene as extraction solvent, 1.3 mL of ethanol as dispersive solvent and 3 min of extraction time for UADLLME. In the case of MAE, extraction temperature of 70 °C, extraction time of 4 min and solvent-to-materials ratio of 40:1 were adopted. Results demonstrated that the proposed method had good performance with linearity of 0.0050–4.98 mg/L, recovery of 83.3–91.5%, RSDs below 5.6% and detection limit (LOD) of 1.15–2.46 μg/L for six pyrethroids, offering higher extraction efficiency and larger enrichment factor. MAE-UADLLME provided a sensitive and efficient alternative to determination of trace amounts of pesticides residues in food samples.